(3CQHYhf ShQI ef RHhQ OGhO Ydjg GdSdGes - (3cdGe Gddg YR hLds
(3ChdgG (B:s
(3GdShQI GdChdi , HSe Gddg GdQMef GdQMje , YLHkG def Cjbf HGdehJ cSa jaQM , hYLHkG def Cjbf HGdBNQI cja jVMc s
(3BNQgG (B:s
(3ef GdShQI GdCQHYjf bhdg (B: (3jGHf BOe dGJYUjfi hdG JfSGfi , hdG JNGdafi hdGJHYO Yfi hGLYd OfjGc YSQkG hQRbc bdjdkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3cJHJ GdYfGhjf HGdMeQI Ch GdUaQIs
(3eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds